Clinical Characteristics of Gastric Duplication in Children - Liu, Fei; Xu, Xiaogang; Lan, Menglong; Tao, Boyuan; Liang, Zijian; Zeng, Jixiao (Frontiers in Pediatrics, 2022)
Background To investigate the clinical characteristics of gastric duplication (GD) in children. Methods The clinical data of 17 children with GD who were treated in our hospital from July 2015 to June 2021 were analyzed retrospectively. There were 8 males and 9 females, aged from 2 months to 11 years. All children underwent laparoscopic GD resections and postoperative pathological diagnosis was GD. In addition, we searched and analyzed the literature on GD in children from 1 January 2011 to 31 December 2021 from the PubMed, EMBASE, and Cochrane Library databases. Results Gastric duplication was more common in females, with the most common cystic type occurring in the greater curvature of the stomach. Vomiting is the most common clinical manifestation. Ultrasound is an effective method for the early screening of GD. In this study, one patient who had multiple GDs underwent laparoscopic cystectomy and mucosectomy, one patient was converted to open surgery, and all other children underwent laparoscopic cystectomies. The time to oral intake was 2.3 ± 1.0 days (range: 1–4 days), and the postoperative hospital stay was 5.7 ± 1.7 days (range: 2–9 days). All children were followed up for 6–77 months and had an uneventful recovery with the resolution of the preoperative symptoms. Conclusion Gastric duplication in children lacks specific clinical manifestations, and the preoperative diagnosis rate is not high, so surgical exploration combined with pathological examination is often needed to make a clear diagnosis. Laparoscopic cystectomy can achieve good therapeutic results.